FAKTOR-FAKTOR YANG MEMPENGARUHI BEBAN RANCANGAN (DESIGN LOAD) TERKAIT DENGAN PERHITUNGAN KONSTRUKSI KAPAL- KAPAL NIAGA BERBAHAN BAJA MENURUT REGULASI KLAS - Iswadi Nur (Bina Teknika, 2015)
The ships construction system must be hold against the inside force of ship although the outside force of ship. The inside force of ship come from the the force of ships lightweight components, and the force ships deadweight components. While the outside force of ship come from the sea water wave and the air flow against the ships hull when the ship is sailing. The influence factors of design load of ships construction calculation such as: the kind of ship, the load force against the ships hull, the length area of ship likes after peak, middle, and fore peak, the area of sea water, the comparison of ships dimension (length/depth), the kind of steel, and the corrosion of steel